Dendritic bundles, minicolumns, columns, and cortical output units - Innocenti, Giorgio; Vercelli, Alessandro (Frontiers in Neuroanatomy, 2010)
The search for the fundamental building block of the cerebral cortex has highlighted three structures, perpendicular to the cortical surface: i) columns of neurons with radially invariant response properties, e.g., receptive field position, sensory modality, stimulus orientation or direction, frequency tuning etc. ii) minicolumns of radially aligned cell bodies and iii) bundles, constituted by the apical dendrites of pyramidal neurons with cell bodies in different layers. The latter were described in detail, and sometimes quantitatively, in several species and areas. It was recently suggested that the dendritic bundles consist of apical dendrites belonging to neurons projecting their axons to specific targets. We review the concept above and suggest that another structural and computational unit of cerebral cortex is the cortical output unit (COU), i.e. an assembly of bundles of apical dendrites and their parent cell bodies including each of the outputs to distant cortical or subcortical structures, of a given cortical locus (area or part of an area). This somato-dendritic assembly receives inputs some of which are common to the whole assembly and determine its radially invariant response properties, others are specific to one or more dendritic bundles, and determine the specific response signature of neurons in the different cortical layers and projecting to different targets.